2002
DOI: 10.1197/aemj.9.3.209
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology and Diagnosis of Penetrating Eye Injuries

Abstract: It is estimated that there are 3.1 penetrating eye injuries per 100,000 person‐years in the United States. Objectives: To evaluate the epidemiology of penetrating eye injuries and to identify physical examination findings that facilitate the diagnosis and ophthalmologic referral of patients with these injuries. Methods: This was a retrospective chart review of emergency department patients with penetrating eye injuries seen for evaluation from July 1987 to January 1999. The setting was a tertiary referral, uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 19 publications
3
14
0
Order By: Relevance
“…Srivastava et al found in their study that males are more affected [14]. Other studies have also proved same findings [15][16][17]. In our study blunt trauma accounts for traumatic cataract in 37.5% and penetrating trauma in 62.5% of cases.…”
Section: Discussionsupporting
confidence: 88%
“…Srivastava et al found in their study that males are more affected [14]. Other studies have also proved same findings [15][16][17]. In our study blunt trauma accounts for traumatic cataract in 37.5% and penetrating trauma in 62.5% of cases.…”
Section: Discussionsupporting
confidence: 88%
“…The male preponderance in this study is similarly found in many studies [5,[13][14][15][16][17]. Reasons for the male preponderance have been well documented in the literature being that males are more involved in riskladened activities than their female counterparts [16,18].…”
Section: Discussionsupporting
confidence: 86%
“…2 Despite the public health significance of this problem, there have been a few population-based studies on prevalence and risk factors of ocular trauma, with most studies from Western countries. [3][4][5][6] Studies in Asia are emerging, 7,8 but there have been no previous epidemiological study of ocular trauma and its risk factors conducted in urban Asian environments.…”
Section: Introductionmentioning
confidence: 99%